Evolution of the ECB's analytical framework - Fédéric Holm-Hadulla; Alberto Musso; Diego Rodriguez Palenzuela; Thomas Vlassopoulos (European Central Bank (ECB), 2021)
This paper discusses the role of economic and monetary analysis in the monetary policy strategy of the European Central Bank (ECB). Both areas of analysis have evolved since the 2003 strategy review. Economic analysis has assigned an increasingly relevant role to the Eurosystem and ECB staff macroeconomic projections in forming a view on the medium-term outlook for economic activity and inflation. Furthermore, its focus has strengthened with regard to structural trends in shaping key economic relationships. Similarly, monetary analysis has shifted in focus: while the 2003 review emphasised the information value of monetary dynamics for detecting risks to price stability over medium-term to longer-term horizons, the focus of monetary analysis has increasingly been redirected to the assessment of monetary policy transmission. This evolution has opened a gap between the formal description of the strategy following the 2003 review and the practice of economic and monetary analysis in informing the ECB's policy deliberations. This paper concludes by presenting options for closing this gap and aligning the strategy formulation with the evolved role of economic and monetary analysis.
Keywords: E32; E37; E44; E47; E51; E52; E58; 330; Economic analysis; monetary analysis; ECB two-pillar framework